2014
DOI: 10.1002/ijch.201400036
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM through the 1990s: The First Twenty Years of Method Development and Applications

Abstract: The 2013 Nobel Prize in Chemistry was awarded to the authors of the first two publications utilizing the concept of combined quantum mechanical and molecular mechanical (QM/MM) methods. In celebrating this great event in computational chemistry, we review the early development of combined QM/MM techniques and the associated events that took place through the mid-1990s. We also offer some prospects for the future development of quantum mechanical techniques for macromolecular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 160 publications
0
44
0
Order By: Relevance
“…Although it is possible to treat an entire enzyme–solvent system by QM methods (Car & Parrinello, 1985; Gao, Zhang, et al, 2014; Rohrig, Guidoni, & Rothlisberger, 2005; Stewart, 1996; Titmuss, Cummins, Rendell, Bliznyuk, & Gready, 2002), the computational costs are still too large to be practical for free energy simulations of enzymatic reactions. The most effective approach to model chemical reactions both in condensed phases and in enzymes is QM/MM methods (Liu et al, 2014), which offer the advantage of both computational efficiency and accuracy (Gao, 1995a). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is possible to treat an entire enzyme–solvent system by QM methods (Car & Parrinello, 1985; Gao, Zhang, et al, 2014; Rohrig, Guidoni, & Rothlisberger, 2005; Stewart, 1996; Titmuss, Cummins, Rendell, Bliznyuk, & Gready, 2002), the computational costs are still too large to be practical for free energy simulations of enzymatic reactions. The most effective approach to model chemical reactions both in condensed phases and in enzymes is QM/MM methods (Liu et al, 2014), which offer the advantage of both computational efficiency and accuracy (Gao, 1995a). …”
Section: Methodsmentioning
confidence: 99%
“…In QM/MM methods, a system is divided into a QM region and an MM region (Field, Bash, & Karplus, 1990; Gao, 1992, 1995a; Gao & Xia, 1992; Liu et al, 2014; Singh & Kollman, 1986; Warshel & Levitt, 1976). The QM region typically includes atoms that are directly involved in the chemical step and they are treated explicitly by an electronic structure method, whereas the MM region consists of the rest of the system that is approximated by an MM force field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to limited computational power, and a number of problems in the original formulation of the method, QC/MM potentials were not widely used until the 1990s, after significant methodological developments by Singh and Kollman [54], and by Bash, Field and Karplus [55,56]. A recent review highlighting the history of QC/MM methods until the mid-1990s can be found in Liu et al [57]. Since then they have become indispensable for studying many problems, including reactions and other localized quantum processes, such as electronic excitation, in the heterogeneous condensed phase.…”
Section: Including the Environmentmentioning
confidence: 99%
“…[ 11,12 ] Although MMFF and combined QM/MM potentials are computationally efficient for studies of equilibrium properties and chemical reactions, there are also a number of well‐known limitations, preventing their further improvements without introducing problem‐dependent optimizations. [ 13 ] The latter is neither practical, nor desirable for rapid, high through‐put screening purposes and for understanding biomolecular interactions. [ 14 ] The origin of these limitations is rooted in the classical mechanical approximations to quantum mechanics of the potential energy surface.…”
Section: Introductionmentioning
confidence: 99%